Patient-specific instrumentation does not improve radiographic alignment or clinical outcomes after total knee arthroplasty: A meta-analysis - Huijbregts, H.; Khan, R.; Sorensen, E.; Fick, Daniel; Haebich, S. (2016)
© 2016 The Author(s). Published by Taylor & Francis on behalf of the Nordic Orthopedic Federation.Background and purpose — Patient-specific instrumentation (PSI) for total knee arthroplasty (TKA) has been introduced to improve alignment and reduce outliers, increase efficiency, and reduce operation time. In order to improve our understanding of the outcomes of patient-specific instrumentation, we conducted a meta-analysis. Patients and methods — We identified randomized and quasi-randomized controlled trials (RCTs) comparing patient-specific and conventional instrumentation in TKA. Weighted mean differences and risk ratios were determined for radiographic accuracy, operation time, hospital stay, blood loss, number of surgical trays required, and patient-reported outcome measures. Results — 21 RCTs involving 1,587 TKAs were included. Patient-specific instrumentation resulted in slightly more accurate hip-knee-ankle axis (0.3°), coronal femoral alignment (0.3°, femoral flexion (0.9°), tibial slope (0.7°), and femoral component rotation (0.5°). The risk ratio of a coronal plane outlier (> 3° deviation of chosen target) for the tibial component was statistically significantly increased in the PSI group (RR =1.64). No significance was found for other radiographic measures. Operation time, blood loss, and transfusion rate were similar. Hospital stay was significantly shortened, by approximately 8 h, and the number of surgical trays used decreased by 4 in the PSI group. Knee Society scores and Oxford knee scores were similar. Interpretation — Patient-specific instrumentation does not result in clinically meaningful improvement in alignment, fewer outliers, or better early patient-reported outcome measures. Efficiency is improved by reducing the number of trays used, but PSI does not reduce operation time.